An Inside View of Congressional Campaigning on the Web. Issue 4 (2nd October 2018) - Druckman, James N.; Kifer, Martin J.; Parkin, Michael; Montes, Ivonne
Abstract : This paper offers an insider perspective of United States Congressional campaigning by exploring political marketing on the web. We offer theoretical frameworks that predict how campaigns view their websites (e.g., perceptions of likely audiences), how campaigns use their websites (e.g., content posted), and how these views and usages have evolved (or not) over time. We test our predictions with a unique data set from surveys of political marketers involved with the creation and maintenance of congressional campaign websites between 2008 and 2014. Consistent with our expectations, we find uniform views across campaigns about perceived website users (e.g., engaged voters). However, we also find support for our expectation of fundamental differences—between incumbent and non-incumbent campaigns—in what is posted on campaign websites. We also find some, but not many, changes in website usage over time. We conclude that differential marketing motivations result in campaigns that depart from the normative ideal of engaged dialogues that facilitate representation.